Eurhamphus pancinii, a new species of the genus Eurhamphus Shuckard, 1838 (Coleoptera: Curculionidae: Molytinae: Orthorhinini) from West Papua - Anderson, Robert S. (Zootaxa, 2019)
Eurhamphus pancinii n. sp. is described based on a series of specimens collected in West Papua, in the Arfak Mountains and on Yapen Island. The only other species in the genus is Eurhamphus fasciculatus Shuckard known from New South Wales northwards into Queensland in Australia. The new species is distinguished from E. fasciculatus by the pronotum and elytra with the glabrous raised areas between the rows of scales very narrow, and elytra with sutural and interstria 3 low and evenly rounded throughout length, elytra in profile not humped towards base (both sexes), and in males by a shorter, less strongly dorsally granulate rostrum, front and middle tibia with inner margins with a very small subapical tooth, and inner edge of front tibia with only a few short, subapical hairs. Eurhamphus fasciculatus is associated with Hoop Pine, Araucaria cunninghamii and although no plant associations are available for specimens of the new species it is expected to be similarly associated with Araucaria.